FIRM CHARACTERISTICS AND COMPLIANCE WITH OPERATING SEGMENT DISCLOSURES BASED ON PSAK 5 - Khairina Nur Izzaty; Yanti Pujiastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study is to find empirical evidence of the influence of company characteristics and disclosure practices of segments of manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the factors that affect the level of segment disclosure of these companies. Consistent with previous research related to segment disclosure, in this study, the level of segment disclosure was tested using a disclosure index based on the mandatory requirements in the Statement of Financial Accounting Standards (PSAK) 5 Operating Segments. The results showed that the average level of segment disclosure with a sample of 88 manufacturing companies listed on the IDX from 2016 to 2018 was 51.2% with a range between 12.5% to 91.7%. Users of financial statements from the sample firms expect broader segment disclosure from the larger, more leveraged firms. Furthermore, the results of the study confirm that industry competition, profitability and earnings quality do not have a significant effect on the level of segment disclosure. These results can provide feedback to regulators in Indonesia regarding current segment disclosure practices by companies listed on the IDX as well as the factors that affect the level of segment disclosure.